Pengaruh Motivasi Kerja, Disiplin Kerja, dan Lingkungan Kerja terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Intervening pada PT. PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Tanjungpinang - Molly, Sisca Dewi; Indrayani, Indrayani; Yasa, I Wayan Catra (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The aim of this research is to determine and analyze the influence of work motivation, work discipline and work environment on employee performance with job satisfaction as an intervening variable at PT. PLN (Persero) Tanjungpinang Customer Service Implementation Unit (UP3). The method used in this research is a quantitative method. The type of data used in this research is primary data. The respondents of this research are employees of PT. PLN (Persero) UP3 Tanjungpinang took 108 samples using a saturated sampling technique. The data collection method was carried out by distributing questionnaires using the SEM-PLS Version 3.0 application. The results of this research found that partially the work motivation and work discipline variables did not have a significant influence on job satisfaction, but the work environment variables had a significant influence on job satisfaction among PT employees. PLN (Persero) UP3 Tanjungpinang. On the other hand, work motivation, work environment and job satisfaction variables have a significant influence on performance, but work discipline variables do not have a significant influence on employee performance at PT. PLN (Persero) UP3 Tanjungpinang. Interveningly, the variables of motivation and work discipline do not have a significant influence on employee performance through job satisfaction, only work environment variables have a significant influence on employee performance through employee job satisfaction at PT. PLN (Persero) UP3 Tanjungpinang.